2016
DOI: 10.3889/oamjms.2016.059
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postoperative Pulmonary Complications after Abdominal Surgery

Abstract: BACKGROUND:Incidence of postoperative pulmonary complications (PPC) in patients undergoing non-cardiothoracic surgery remains high and the occurrence of these complications has enormous implications for the patient and the health care system.AIM:The aim of the study was to identify risk factors for PPC in patients undergoing abdominal surgical procedures.MATERIALS AND METHODS:A prospective cohort study in abdominal surgical patients, admitted to the emergency and surgical ward of the UHC of Tirana, Albania, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 20 publications
4
19
0
1
Order By: Relevance
“…The risk factors for development of PPCs from our study were found to be incision type, presence of comorbidities, duration of surgery, length of critical care stay, and hospital stay. These findings were also reported in other studies which looked at predictors of PPCs in patients (Rudra and Das 2006 ; Jensen and Yang 2007 ; Denu et al 2015 , Kodra, Shpata and Ohri 2016 ). Gender, age over 65 years and category of surgery were not found to be associated with development of PPCs in our study contrary to other studies (Jensen and Yang 2007 , Denu et al, 2015 , Kodra, Shpata and Ohri 2016 ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The risk factors for development of PPCs from our study were found to be incision type, presence of comorbidities, duration of surgery, length of critical care stay, and hospital stay. These findings were also reported in other studies which looked at predictors of PPCs in patients (Rudra and Das 2006 ; Jensen and Yang 2007 ; Denu et al 2015 , Kodra, Shpata and Ohri 2016 ). Gender, age over 65 years and category of surgery were not found to be associated with development of PPCs in our study contrary to other studies (Jensen and Yang 2007 , Denu et al, 2015 , Kodra, Shpata and Ohri 2016 ).…”
Section: Discussionsupporting
confidence: 85%
“…Studies conducted in low-income countries showed that 10–15% of hospital admissions were due to diseases amenable to surgical treatment, of which diseases were more prevalent in the young population compared to high income countries (Hanekom, Coetzee and Faure 2006 , Frankel et al, 2007 , Semer, Sullivan and Meara 2010 , Chalya et al, 2011 , Pearse et al, 2012 , Kodra, Shpata and Ohri 2016 ) and the same pattern was noted in the current study. The affected age group in African countries of between 15 and 44 years is the predominant economically active segment of the population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time a patient remains anesthetized is directly related to the frequency of complications; hypothermia, deep venous thrombosis, pulmonary thromboembolism, changes in coagulation, bleeding, alterations in the immune system, and neurovascular compressions are some of the usual drawbacks in prolonged surgery-anesthesia [26]. In plastic surgery, there are procedures that require prolonged times such as patients with combined surgeries and postbariatric cases with large weight loss.…”
Section: Surgery Timementioning
confidence: 99%
“…The estimated incidence of PPCs varies greatly, ranging from as low as 5% to as high as 70%, depending on the type of surgery, which PPCs are included in the estimate and the study population [2]. PPCs are particularly common among patients who have undergone cardiac [3], thoracic [4] or upper abdominal surgery [5], and the patient's underlying pulmonary status and comorbidities are just a few of the many factors which contribute to the individual's risk of PPC after surgery [2].…”
Section: Introductionmentioning
confidence: 99%